Microsoft Office 2000 - David W. Beskeen (Course Technology, 2000)
Instructor's Resource Kit(Electronic Instructor's Manual with lecture notes, Teaching Tips, Upgradeer's Guide, Sample Syllabus, Extra Independent Challenges and solutions, Figure Files, Solution Files, Course Test Manager and Testbank, Learning Microsoft Outlook 2000 E-Mail): ISBN 0-7600-6112-2; Review Pack (Project Files, Learning Microsoft Outlook E-Mail): ISBN 0-7600-6113-0; Faculty and Student Online Companions